Research Progress on Thermal Runaway Protection of Lithium-Ion Power Battery - Zhai, Jiawei; Wang, Jiajun; Lei, Zhiguo (Current Materials Science, 2023)
The attention to electric vehicle (EV) development is still a hot topic. As an important part of EV - power battery, its safety issue is still a major concern. The most recent research on TR mechanism, inducement, and transmission is initially presented, and then the most recent research status on TR protection is partially expanded using these concepts. Then the influence of the material and design of the battery cell components on TR is introduced, and lastly, the safety measures before and after TR are comprehensively reviewed. This paper serves as a summary of previous TR research as well as a reference for future TR protection.
Keywords: battery safety